Trapped Between Ableism and Neoliberalism: Critical Reflections on Disability and Employment in India - Kumar, Arun; Sonpal, Deepa; Hiranandani, Vanmala (Disability Studies Quarterly, 2012)
Despite affirmative actions such as reservations in government employment, incentives and subsidies to employers, tax exemptions to persons with disabilities, skill-development trainings etc, employment for persons with disabilities continues to be characterised by lower work-force participation, lower wages, lack of career advancement opportunities, and discrimination at the workplace. Simultaneously, social security benefits have been declining due to shrinking state role. With the ratification of the UNCRPD, preparation of the new disability legislation and increasing pressure from the disability rights movement in India, questions of work and employment have begun to gain attention. Using a case study approach, this article interrogates the outcomes of three employment initiatives in India. We contend that while access to employment opportunities for persons with disabilities may have increased, the responses remain trapped in constructs of ableism and the outcomes adversely affected by neoliberalism. The article calls for developing a more critical research agenda and building capacities for wider contestation against ableism and neoliberalism. Keywords: ableism, employment, disability rights, India, neoliberalism